Small islands, valuable insights: systems of customary resource use and resilience to climate change in the Pacific - McMillen, Heather L.; Ticktin, Tamara; Friedlander, Alan; Jupiter, Stacy D.; Thaman, Randolph; Campbell, John; Veitayaki, Joeli; Giambelluca, Thomas; Nihmei, Salesa; Rupeni, Etika; Apis-Overhoff, Lucille; Aalbersberg, William; et al. (Ecology and society, 2014)
Understanding how social-ecological systems are and can be resilient to climate change is one of the world's most crucial problems today. It requires knowledge at local and global scales, the integration of natural and social sciences, and a focus on biocultural diversity. Small Pacific Islands and the knowledge-practice-belief systems of their peoples have a long history of resilience to environmental variability and unpredictability, including in areas with marginal habitats and with periodic, severe disturbance (e.g., drought, flood, storms, and tsunami). We review the state of research on these knowledge systems as it pertains to resilience and adaptation, and we highlight critical research needs to address the interrelated areas of: (1) local-scale expertise and observations of change with regard to weather, life-history cycles, and ecological processes; (2) customary resource management institutions and practices (i.e., with agroforests and the nearshore marine environment); and (3) the roles of leaders, social institutions, and social networks in the context of disturbance and change. We conclude that these knowledge systems can contribute high-resolution observations, benchmark data, and insights into practices that enhance resilience and adaptive capacity in integrated terrestrial and marine systems. Community-based and participatory approaches can complement and ground-truth climate models and direct culturally appropriate resource management, research, and adaptation measures. Although most islands in the Pacific are small, their knowledge systems include valuable insights on seasonal cycles, ecological processes, and the management of biocultural diversity that are relevant at a broad scale for understanding resilience and adaptability to the social-ecological effects of climate change.